THE SHARED SPACE STREET FACTORS OF COMMERCIAL CORRIDOR IN PEMUDA STREET, MAGELANG CITY - Marcelina Dwi Setyowati (ARSITEKTURA, 2018)
Shared space street design is a concept that eliminates the segregation and physical marker of the path difference of a street corridor, creating uncertainty that will make the rider reduce the speed of his vehicle, those required to be more tolerant with other users. Aims to reduce the dominance of vehicles by sharing road space between pedestrians, non-motorized vehicles and motor vehicles, but pedestrians are a primary priority. The existing condition of Pemuda street corridor, which is a commercial corridor in Magelang city, shows that the dominance of existing motor vehicles resulted in the movement of pedestrians from the western sidewalk to the eastern sidewalks are limited, resulting in a gap in the number of pedestrians on each sidewalk. Since 2011 until now Pemuda street Corridor has sidewalks on the eastern which concept is to be in one lane with non-motorized lanes (pedicabs, bicycles, carts etc.), so it has a width of up to 5 meters. It shows the characteristics that lead to the concept of shared space street. The purpose of this research is to find the factors that can influence the development of shared space street concept in order to solve the problems that arise. The research method used is qualitative deductive method. This research found that the factors that influence the development of shared space street in Pemuda street are comfort, connectivity, diversity, livability, and identity